Phase-steepened Alfven waves, proton perpendicular energization and the creation of magnetic holes and magnetic decreases: The ponderomotive force - Tsurutani, Bruce T.; Dasgupta, B.; Galvan, C.; Neugebauer, M.; Lakhina, G. S.; Arballo, J. K.; Winterhalter, D.; Goldstein, B. E.; Buti, B. (My University, 2002)
[1] Solar wind protons detected within Magnetic Holes (MHs) and Magnetic Decreases (MDs) are found to be preferentially heated perpendicular to equation image0. The MHs/MDs are associated with the phase-steepened edges of nonlinear Alfvén waves. The proton anisotropies can lead to the proton cyclotron and mirror mode plasma instabilities. We examine the Ponderomotive Force (PF), a phenomenon due to wave pressure gradients, and show that for this plasma regime and for phase-steepened Alfvén waves, the PF proton acceleration/energization will primarily be orthogonal to B0. It is suggested that accelerated ions create the MHs/MDs by a diamagnetic effect.
Keywords: Alfven waves; Ponderomotive force; Magnetic holes; Magnetic Decreases; Diamagnetic effect; Interplanetary physics